Solvent-Free Pivalic Acid/Copper Chloride Jointly Promoted Chlorination of 1,2,3-Triazoles - Menendez, Christophe; Saffon, Nathalie; Lherbet, Christian; Baltas, Michel (Synlett, 2012)
A novel chlorination reaction on the 5-position of 1,2,3-triazoles, directly from 5H-substituted 1,2,3-triazoles was developed by using copper(II) chloride in pivalic acid. A series of triazoles were thus chlorinated in low to good yields.
Keywords: chlorination; triazole; copper chloride; pivalic acid